Becenzūrinės komunistinės literatūros leidimas legaliose spaustuvėse Lietuvoje 1919–1934 metais - Žeimantas, Viktoras (Knygotyra, 1973)
The article presents an analysis of the production of the printing-house of Savičas and Šumkauskas in Raseiniai, of the printing – house Jewish Culture League, of „Kibirkštis“ (of G. Levinas) and of some other Kaunas printing-offices, which evading bourgeois censorhip, published Communist literature at various times of the indicated period.